Gibberellin-mediated proteasome-dependent degradation of the barley DELLA protein SLN1 repressor. - Fu, X; Richards, D; Ait-Ali, T; Hynes, L; Ougham, H; Peng, J; Harberd, N (2002)
DELLA proteins are nuclear repressors of plant gibberellin (GA) responses. Here, we investigate the properties of SLN1, a DELLA protein from barley that is destabilized by GA treatment. Using specific inhibitors of proteasome function, we show that proteasome-mediated protein degradation is necessary for GA-mediated destabilization of SLN1. We also show that GA responses, such as the aleurone alpha-amylase response and seedling leaf extension growth, require proteasome-dependent GA-mediated SLN1 destabilization. In further experiments with protein kinase and protein phosphatase inhibitors, we identify two additional signaling steps that are necessary for GA response and for GA-mediated destabilization of SLN1. Thus, GA signaling involves protein phosphorylation and dephosphorylation steps and promotes the derepression of GA responses via proteasome-dependent destabilization of DELLA repressors.